Cultivating conscience : how good laws make good people - Stout, Lynn A., 1957- (Princeton University Press, 2011)
Contemporary law and public policy often treat human beings as selfish creatures who respond only to punishments and rewards. Yet every day we behave unselfishly--few of us mug the elderly or steal the paper from our neighbor's yard, and many of us go out of our way to help strangers. We nevertheless overlook our own good behavior and fixate on the bad things people do and how we can stop them. In this pathbreaking book, acclaimed law and economics scholar Lynn Stout argues that this focus neglects the crucial role our better impulses could play in society. Rather than lean on the power of gre.